Application of Cash Base and Accrual Base on Al-Murabahah Financing in Muamalat Bank Indonesia - Herzeqovina, Berlian (Journal of Islamic Economic Scholar, 2020)
This research is motivated by the need to record every trade, as mandated in QS Al Baqarah verse 282, so that people who make transactions or invest become safe and lose any doubt. This study aims to determine the Application of Cash Basis and Accrual Basis for al murabaha financing at PT. Bank Muamalat Indonesia and to find out whether it is in accordance with the application of cash basis and accrual basis according to PSAK 102 and PAPSI at PT. Bank Muamalat Indonesia. The data used in this research is secondary data. Data collection techniques are with field research and library research. The research method used is a qualitative method, namely analyzing and describing the application of cash basis and accrual basis for al murabahah financing at PT. Bank Muamalat Indonesia applies Cash Basis and Accrual Basis for recording financial transactions. In Muamalat bank practice, Cash Basis and Accrual Basis are also used for recording income on al-murabahah financing. The use of cash basis in al-murabahah financing is recorded / recorded when the customer makes the disbursement of the financing and the accrual basis is recorded / recorded when the customer makes installment payments from the initial installment to the last installment. And the recognition and measurement of the murabaha profit sharing at PT. BANK MUAMALAT Indonesia has been appropriately applied based on PSAK No. 102 and PAPSI regarding al murabahah accounting. Bank Muamalat Indonesia applies Cash Basis and Accrual Basis for recording financial transactions. In Muamalat bank practice, Cash Basis and Accrual Basis are also used for recording income on al-murabahah financing.Keywords : Accrual Cash, Al Murabahah, Cash Base.